If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8(6x+12)=-32x-24
We move all terms to the left:
-8(6x+12)-(-32x-24)=0
We multiply parentheses
-48x-(-32x-24)-96=0
We get rid of parentheses
-48x+32x+24-96=0
We add all the numbers together, and all the variables
-16x-72=0
We move all terms containing x to the left, all other terms to the right
-16x=72
x=72/-16
x=-4+1/2
| a=12,2a-6 | | u-1.3=9.37 | | x+6=-8. | | 3-7n+5n=7 | | -x/3-12=40 | | P=3x/2+5x | | -7=-8+n4 | | 8-3r=-5r+1+5 | | 180=124+3y-11 | | 11x+57=180 | | 2q6=4 | | –8.46=–2.1n–2.16 | | t-3/5=1/5 | | 0.875b-32=0.75b=32 | | -2s+1=13 | | -3.6x-7.2=-12.7-6.1x | | a=122a-6 | | 16.35=39.75-x | | f+10=17.87 | | 2x^{2}+3x-4=0 | | 17n=340 | | 150+10p=200+5p | | x+37.1=72.8 | | y-3=2.9 | | 2a-6a=12 | | -6t-6=18 | | y=-1/4*1+3 | | 4a+3=-9+2a | | 2x-2A=3B | | -9=10x+81 | | 2n+10+4n=15+6n | | 1/5+n=2/5 |